Proyecto de ley n. 14.782 Reforma de los artículos 191, 192 y 215 del Código Penal, Ley n. 4573, de 4 de mayo de 1970 - Costa Rica. Asamblea Legislativa Autoría 46158
Reforma de los artículos 191, 192 y 215 del Código Penal